Development, implementation and evaluation of a hybrid study program for sustainability competencies and future skills - Terpstra-Rundel, Christina; Möller, Clemens (Frontiers in Education, 2025)
IntroductionIndustrialized countries face the challenge of an aging population and declining birth rates, leading to a shortage of qualified personnel. In addition, organizations are confronted with the need for a sustainable transformation, driven by factors such as customer expectations, regulatory requirements, legislative changes, competitive pressures, and societal demands. This leads to increasing demand for, and a shortage of, employees with relevant future skills, particularly in sustainability competencies. Universities are adopting their offers to address these evolving societal and business needs.MethodsThis study presents recent literature on workforce and student demands, with a particular focus on sustainability competencies and flexibility in education, also for addressing needs of lifelong learning. Based on these insights, we conducted a survey targeting current and potential students in a rural, industrial-dominated region in Germany to better understand their expectations and needs.ResultsThe findings informed the development of a Master’s program that emphasizes sustainable development through project-based learning and close collaboration with businesses and organizations. Key features include flexible, blended/hybrid learning approaches and a wide array of elective modules from related degree programs, allowing students to tailor their studies to personal and professional goals while accommodating part-time work or caregiving responsibilities. Student evaluations conducted after the program launch reveal its success in meeting regional and broader student demands. Students highlighted the importance of flexibility, interactive learning, and the integration of interdisciplinary topics. These preferences also underscore the challenges of implementing such a program, particularly the need for effective coordination by both students and the university.Discussion and conclusionWe conclude that the program model is well-suited to addressing current demands. However, it requires ongoing adaptation to ensure sustainable success, also to meet lifelong learning demands by continuously including trends and topics of relevance for the target group.